Immune suppression in the early stage of COVID-19 disease - Wenmin Tian (Nature Portfolio, 2020)
How COVID-19 pathology differs from other drivers of pneumonia is unclear. Here the authors analyze urine from patients with COVID-19 and identify an immunosuppressive protein expression pattern that is distinct from the pattern in healthy individuals or patients with non-COVID-19 pneumonia.